Hur påverkas vård- och terapihundar av sitt arbete och hur uppfattar föraren hundens känslor? - Kindsjö, Jannice (2014)
Today's research on animal assisted interventions (AAI) has focused on the positive effects on humans. Dogs used for AAI are an expanding market, but the research on this area hasn't followed the increasing use. The few studies on dogs in this field mostly observed their cortisol-levels and are very ambiguous. I have observed the behaviour of dogs working with AAI compared to when they are off-duty to see how they are affected by their work. Their handlers where also told to make an assessment of the dog's emotions during the session.